GREEN MOVEMENT OF MUSLIMAT NU: ECOLOGICAL JIHAD BY “SEDEKAH SAMPAH” PROGRAM - Wirawan, Abdul Karim (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This article examines the Ecological Jihad carried out by women's organization of Nahdlatul Ulama called Muslimat NU through Sedekah Sampah (Waste Alms) in Bungah District, Gresik Regency. This movement is a concrete effort to address environmental challenges with a religious approach. This movement not only targets waste reduction but also aims to foster ecological awareness based on spiritual values. This study aims to analyse three main aspects of the movement. First, how does Muslimat NU implement religious values in the context of environmental conservation? Second, the role of Muslimat NU is to increase public awareness of the importance of protecting the environment through waste management activities. Third, the real impact of this movement on environmental awareness in Gresik. This study uses a qualitative descriptive approach with field observation methods, in-depth interviews, and documentation as data collection techniques. The data is analysed to understand the patterns that emerge in the application of religious values ​​and the public's response to this movement. The results of the study indicate that the concept of ecological jihad applied through the waste alms movement has succeeded in motivating the public to care more about the environment, while also having a positive impact on waste reduction in Bungah district.